2021
DOI: 10.2196/27121
|View full text |Cite
|
Sign up to set email alerts
|

Computer Mouse Movements as an Indicator of Work Stress: Longitudinal Observational Field Study

Abstract: Background Work stress affects individual health and well-being. These negative effects could be mitigated through regular monitoring of employees’ stress. Such monitoring becomes even more important as the digital transformation of the economy implies profound changes in working conditions. Objective The goal of this study was to investigate the association between computer mouse movements and work stress in the field. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…stress based on keystroke features in a laboratory study [12]. Although Banholzer et al [13], for example, followed the participants in real life for seven weeks, most of the computer usage studies on stress have been carried out in laboratories [14,15] or have lasted only a short time [11,16]. We observed location independent knowledge workers for five months to explore whether group-level data on mouse and keyboard usage and daily self-reports of stress could be useful as a basis for a long-term assessment of stress in real-life work.…”
Section: Different Methods To Detect Stress In Knowledge Workers: a P...mentioning
confidence: 97%
“…stress based on keystroke features in a laboratory study [12]. Although Banholzer et al [13], for example, followed the participants in real life for seven weeks, most of the computer usage studies on stress have been carried out in laboratories [14,15] or have lasted only a short time [11,16]. We observed location independent knowledge workers for five months to explore whether group-level data on mouse and keyboard usage and daily self-reports of stress could be useful as a basis for a long-term assessment of stress in real-life work.…”
Section: Different Methods To Detect Stress In Knowledge Workers: a P...mentioning
confidence: 97%
“…The emotions of the driver were assessed according to the circumplex model of affect, which is composed of the 2 dimensions arousal and valence [ 33 , 34 ]. The arousal dimension describes the drivers' feeling of being awake, and the valence dimension indicates the corresponding level of happiness.…”
Section: Methodsmentioning
confidence: 99%
“…In another recent study, Banholzer et al concluded that computer mouse can be used to infer work stress [24]. This finding was reported based on a dataset collected from 71 persons using their computers for usual daily work.…”
Section: A Mouse Trajectory Analysismentioning
confidence: 95%